Korelasi Total Lymphocyte Count dengan CD4+ pada Anak Terinfeksi Human Immunodeficiency Virus - Ibrahim, Dewi Ratyh (Universitas Islam Negeri Alauddin Makassar, 2025)
CD4+ T cells are a marker for assessing disease progression in HIV infection, but their cost precludes their use in most parts of the world. On the contrary, Total Lymphocyte Count (TLC) can be used as an alternative. Therefore, this study aimed to investigate the correlation between TLC and CD4+ levels in pediatric HIV patients. This cross-sectional study was conducted from April 2022 to June 2022. The study sample consisted of pediatric HIV patients aged >6 weeks to 17 years and 11 months who were treated at Dr Wahidin Sudirohusodo Makassar from January 2015 to December 2022. Data analysis using SPSS v. 26. The Spearman correlation test was used to determine the correlation of TLC with CD4+. A total of 50 subjects met the inclusion criteria and consisted of 29 (58%) male and 21 (42%) female. The average CD4+ was 423± 642 with a median (min-max) of 127 (1–2,859), and the TLC value showed an average of 2,311±2,360 with a median (min-max) of 1,233 (61–9242). Spearman’s correlation test showed a strong positive correlation between CD4+ cell count and TLC (r=0.775; p<0.001). There is a correlation between TLC and CD4+, so TLC can be used as an additional monitoring indicator of immunodeficiency status to replace CD4+ cells in patients with HIV infection.